Analisis Penerapan Kurikulum pada Pembelajaran Bahasa Arab di MTs Manba'ul 'Ulum Silebu - Hajjin Mabrur; Apip Abdul Latif; Casda Waluya; Lucyana Siti Juliah (Indonesian Journal of Islamic Education Studies (INJURIES), 2023)
The government has implemented the 2013 Curriculum to be tested in several A and B accredited schools, namely in Primary (SD), Secondary (SMP) and Upper (SMA / SMK) education. In Curriculum 2013, to improve the quality of learning cannot be separated from the learning process. The method used in this research is a qualitative method. This method was chosen because it aims to determine how to search, collect, process, and analyze data from the results of the study. The data analysis technique used is SWOT analysis (Strengths, Weaknesses, Opportunities, Threats). SWOT stands for Strengths, Weaknesses, Opportunities, and Threats. The results showed that the strengths of the application of Arabic language learning at MTs Manba'ul 'Ulum are a supportive environment and the large number of students with santri backgrounds, because MTs Manba'ul 'Ulum Silebu itself is a school located in a pesantren environment and under the auspices of the Manba'ul 'Ulum Silebu Islamic Boarding School Foundation. While the weaknesses are: (1) Lack of interest and motivation in learning Arabic (2) Students lack confidence in Arabic (3) Students at MTs Manba'ul 'Ulum are not all santri, so teachers must try to balance the material with students who are not santri. Keywords: Curriculum Implementation; Arabic Language Learning; Madrasah Tsanawiyah.